Investigation of the Level of Susceptibility to Ethical Values of Sports High School Students - Karataş, Emine Öztürk; Karataş, Özgür (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: This study aims to determine the predisposition of students studying at Malatya Sports High School to ethical values. Methods: This is an applied study in the form of a descriptive survey model. The population consists of 371 students who continue their education at Malatya Sports High School in the 2021-2022 academic year, and the sample group consists of randomly selected 188 students at Malatya Sports High School. “Predisposition to Ethical Values Scale” developed by Kaya was used in the study. The Cronbach's Alpha value of the scale was found as 0.89, and the Cronbach's alpha values of the sub-dimensions were determined as 0.80 for 'Love, Respect', 0.86 for 'Justice, honesty' and 0.74 for 'Cooperation'. Results: Following the study, there is no significant difference found in the predisposition of students at Malatya Sports High School to ethical values according to the variables of gender, age, class, educational background of father and mother. A significant difference was found according to the variable of family income. It was determined that this difference emerged between the sub-dimensions of love-respect and justice-honesty. Conclusion: We can say that sports high school students who receive sports training will stay away from unethical behaviors as a result of the positive behaviors they learn from educational activities at school, trainings and their teammates.